Modeling Rumor Diffusion Process With the Consideration of Individual Heterogeneity: Take the Imported Food Safety Issue as an Example During the COVID-19 Pandemic - Chen, Tinggui; Rong, Jingtao; Yang, Jianjun; Cong, Guodong (Frontiers in Public Health, 2022)
This paper integrates the individual’s diffusion willingness, the individual’s forgetting degree, and the intensity of government punishment based on the classic SEIR model and designs an individual state transition mode at first. Secondly, it considers the influence of factors such as the degree of trust among individuals on the rumor diffusion, and constructs an individual information interaction mode. Finally, an improved SEIR model named SEIR-OM model is established, and the generation and diffusion process of rumors are simulated and analyzed from two aspects: model parameter setting and rumor control strategy. The results show that: 1) when the average value of the interest correlation between all individuals and the event that caused the rumors is greater, the information content deviation between the network and the real is lower, but the scope of the rumor diffusion will be wider. 2) The increase of the average degree of network nodes intensifies influence of rumors, but its impact on the diffusion has a peak. 3) Adopting knowledge popularization and punishment and restraint strategies in advance can effectively reduce the influence of rumors after the incident. In addition, the government should enforce rumor-refuting strategies right after the event. Also, the number of individuals who refute rumors must be paid attention to. Finally, the paper verifies the rationality and effectiveness of the SEIR-OM model through the real case from the imported food safety issue during the COVID-19 Pandemic.